JUDGMENT IN MACHINES: THE ETHICAL PRECEDENCE OF ARTIFICIAL INTELLIGENCE IN IAN MCEWAN’S MACHINES LIKE ME - Hlail, Mohanad Abdulkadhim; Ahed, Osamah Abdullah (Journal of Higher Education and Academic Advancement, 2025)
Objective: This paper is based on ethics theory, focusing on Kantian deontological ethics and Utilitarianism, attempting to study the moral ambiguous problems in when machines like me by Ian McEwan. The book raises profound ethical issues about artificial intelligence, human responsibility, and truth. Method: Machines Like Me revolves around a love triangle between a man, a woman and a robot. Reflecting on criteria for differentiating between machines and humans one relatively obvious distinction, which Mills' Machines Like Me prompts, is that between a moral quality of artificial intelligence (AI) and one of human intelligence. Artificial intelligence systems might be queried about whether they might be willing to perform specific tasks. Results: In the analogue of such robots as might today be constructible to answer such questions, and steeped in an ethical world. The ethical analogue for such robots also involves the so-called critical mind process and theory chains behind AIs giving rise to behaviour prototyped and expressed by non-violent method. Novelty: On the practical implementation plane, the question is worked on of the arguments of ethical nature: Reading of a mode of possible state of machine minds have facilitated the cybernetic vision of human minds and then enabled cybernetic Turing mind theory to work forward.